The Impact of Climate Change Community Empowerment in Water Resource Monitoring and the Conservation of the Baumata Karst Area as an Effort to Sustain Spring Water Resources in Kupang Regency - Noni Banunaek; Herry Z Kotta; Woro Sundari; Robertho Kadji; Irene Augusta Boymau; Matilda Metboki; Aisyah Ahmad; Andreas Sinuhaji; Ika Krisnasiwi; Yusuf Rumbino; Rizhard Anselmus Ndolu (Universitas Nusa Cendana, 2026)
Baumata Village, located in Taebenu District, Kupang Regency, East Nusa Tenggara Province, is a karst area that plays a crucial ecological role as a groundwater recharge zone and a major spring water source utilized by local communities and the regional water utility company (PDAM). The Baumata forest area contributes significantly to maintaining hydrological balance; however, increasing human activities may threaten environmental quality and water sustainability. Therefore, strengthening community capacity in forest conservation and participatory water resource monitoring is essential. This community service program was initiated by the Mining Engineering Study Program to improve public awareness regarding the ecological functions of karst ecosystems and forest conservation while providing technical training on spring discharge measurement and rainfall monitoring using ombrometers. The implementation methods included community outreach, technical training, practical demonstrations, installation of rainfall gauges, and mentoring activities. The results indicated a significant improvement in community understanding of the relationship between forest cover, rainfall patterns, and water availability. Community members were able to independently operate discharge measurement instruments and rainfall gauges and understood the importance of regular hydrological data recording. The program successfully fostered collective awareness and active participation in conserving the Baumata forest area as a critical component of the karst hydrological system. This initiative may serve as a sustainable community-based water resource management model for karst regions in Kupang Regency. Keywords: karst area, spring water, forest conservation, water discharge, community empowerment